2018
DOI: 10.1109/jtehm.2018.2875985
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time Predicts Brain–Computer Interface Aptitude

Abstract: There is evidence that 15–30% of the general population cannot effectively operate brain–computer interfaces (BCIs). Thus the BCI performance predictors are critically required to pre-screen participants. Current neurophysiological and psychological tests either require complicated equipment or suffer from subjectivity. Thus, a simple and objective BCI performance predictor is desirable. Neurofeedback (NFB) training involves performing a cognitive task (motor imagery) instructed via sensory stimuli and re-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The ROC analysis showed that patients who could press and release the LeMMS at least 16 times in 30 s were able to use the scanning system. This result is in line with Darvishi et al who demonstrated that simple reaction time is correlated with BCI performance [28]. In other words, the simple reaction time and the Click-Test-30 (a measure analogous to simple reaction times, in our opinion) are compatible tests for predicting people able to operate their communication technology.…”
Section: Discussionsupporting
confidence: 89%
“…The ROC analysis showed that patients who could press and release the LeMMS at least 16 times in 30 s were able to use the scanning system. This result is in line with Darvishi et al who demonstrated that simple reaction time is correlated with BCI performance [28]. In other words, the simple reaction time and the Click-Test-30 (a measure analogous to simple reaction times, in our opinion) are compatible tests for predicting people able to operate their communication technology.…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive and neurological factors including functions and anatomy along with emotional and mental processes give rise to intra-and inter-subject variability affecting the performance of SMR-based BCI (Wens et al, 2014;Reichert et al, 2015;Zhang et al, 2015;Acqualagna et al, 2016;Betzel and Bassett, 2017;Vasilyev et al, 2017;Seghier and Price, 2018;Betzel et al, 2019;Smith et al, 2019). Time-variant cognitive factors such as fatigue, memory load, attention and reaction time modulate instantaneous brain activity, and can cause inconsistent SMRbased BCI performance (Hammer et al, 2012;Ahn and Jun, 2015;Fox et al, 2015;Jeunet et al, 2015;Darvishi et al, 2018;Sannelli et al, 2019). Furthermore, users' characteristics such as lifestyle, gender, and age can influence BCI performance (Ahn and Jun, 2015).…”
Section: Bci Performance Predictorsmentioning
confidence: 99%
“…Therefore, the relationship between spatial abilities and MI-BCI performance should be further validated in future experiments. It would be interesting to look also at reaction times of the test, as Darvishi et al (2018) showed that scores on the reaction time test are related to BCI performance.…”
Section: Spatial Abilitiesmentioning
confidence: 99%